ETHICS OF STATE OFFICIALS - Raharjo, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2018)
High expectation towards state officials’ behavior seems to be suppressed again. It is because of the following recent case of “papa minta saham (dad asks for shares)” that ends with the change of Minister of Energy and Mineral Resources. It is also interspersed by some behaviors of other state officials in legislative sphere such as corruption as well as decency. The newest case re-appears, even no kiddingly, an official such as head of Constitutional Court does it.........